Cervical cancer prevention program in Mexico disrupted due to COVID-19 pandemic: Challenges and opportunities - Cruz-Valdez, Aurelio; Palacio-Mejía, Lina Sofia; Quezada-Sánchez, Amado D.; Hernández-Ávila, Juan Eugenio; Galicia-Carmona, Tatiana; Cetina-Pérez, Lucely del Carmen; Arango-Bravo, Eder A.; Isla-Ortiz, David; Aranda-Flores, Carlos E.; Uscanga-Sánchez, Santos-Regino; Madrid-Marina, Vicente; Torres-Poveda, Kirvis (Frontiers in Oncology, 2023)
Introduction. The COVID-19 pandemic disrupted the preventive services for cervical cancer (CC) control programs in Mexico, which will result in increased mortality. This study aims to assess the impact of the pandemic on the interruption of three preventive actions in the CC prevention program in Mexico. Methods. This study is a retrospective time series analysis based on administrative records for the uninsured population served by the Mexican Ministry of Health. Patient data were retrieved from the outpatient service information system and the hospital discharge database for the period 2017–2021. Data were aggregated by month, distinguishing a pre-pandemic and a pandemic period, considering April 2020 as the start date of the pandemic. A Poisson time series analysis was used to model seasonal and secular trends. Five process indicators were selected to assess the disruption of the CC program, these were analyzed as monthly data (N=39 pre-pandemic, N=21 during the pandemic). HPV vaccination indicators (number of doses and coverage) and diagnostic characteristics of CC cases were analyzed descriptively. The time elapsed between diagnosis and treatment initiation in CC cases was modeled using restricted cubic splines from robust regression. Results. Annual HPV vaccination coverage declined dramatically after 2019 and was almost null in 2021. The number of positive Papanicolaou smears decreased by 67.8% (90%CI: -72.3, -61.7) in April–December 2020, compared to their expected values without the pandemic. The immediate pandemic shock (April 2020) in the number of first-time and recurrent colposcopies was -80.5% (95%CI:−83.5, −77.0) and -77.9% (95%CI: −81.0, −74.4), respectively. An increasing trend was observed in the proportion of advanced stage and metastatic CC cases. The fraction of CC cases that did not receive medical treatment or surgery increased, as well as CC cases that received late treatment after diagnosis. Conclusions. Our analyses show significant impact of the COVID-19 pandemic with declines at all levels of CC prevention and increasing inequalities. The restarting of the preventive programs against CC in Mexico offers an opportunity to put in place actions to reduce the disparities in the burden of disease between socioeconomic levels.